Association between Ichthyocladius (Diptera: Chironomidae) and armored catfishes in the Guareí River basin, São Paulo State, Brazil - Azevedo-Santos, Valter M. [UNESP]; Shimabukuro, Erika M.; Pelicice, Fernando M.; Henry, Raoul [UNESP] (FapUNIFESP (SciELO), 2022)
Ichthyocladius is a genus of chironomid (Diptera, Insecta) whose immature forms live attached to the bodies of some species of freshwater fishes. Here we investigate the association between Ichthyocladius spp. and armored catfish in streams of the Guareí River basin, Paraná River system, Brazil. We provide the first record of I. lilianae associated with fish in the São Paulo State and the Paraná River basin. In addition, this is the first report of Ichthyocladius associated with the armored catfishes Hypostomus iheringii and H. tietensis. Lastly, we record two undescribed species of Chironomidae (i.e., Ichthyocladius sp. 1 and Ichthyocladius sp. 2) associated with fishes.
Keywords: fish fins; insects; larvae; Loricariidae; pupae; Upper Paraná River basin